2019
DOI: 10.1177/0734242x19862042
|View full text |Cite
|
Sign up to set email alerts
|

Solid waste management practice in a tourism destination – The status and challenges: A case study in Hoi An City, Vietnam

Abstract: This study aims to present waste characterisation, solid waste management practice and analyse the challenges in the solid waste management system in the tourism destination of Hoi An City, Vietnam. The sampling and questionnaire surveys were conducted for measuring characterisation and management practice of solid waste. A material flow analysis method was used for analysing the waste flow. The results show that the tourism destination generated daily around 15080 kg t of waste, in which the significant propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…An insufficient volume of food waste generation was offered as a reason for not recycling. Other studies have experienced the same argument [47][48][49]. However, this study found that the volume of food waste estimates given by businesses who were recycling were roughly the same as business not recycling.…”
Section: Challenges Of Food Waste Recyclingsupporting
confidence: 50%
“…An insufficient volume of food waste generation was offered as a reason for not recycling. Other studies have experienced the same argument [47][48][49]. However, this study found that the volume of food waste estimates given by businesses who were recycling were roughly the same as business not recycling.…”
Section: Challenges Of Food Waste Recyclingsupporting
confidence: 50%
“…The aim of the work is to assess the behaviour of the citizens concerning the formal recycling points available in the city, comparing the results obtained with another survey conducted in parallel within the same municipality. The questionnaire surveys investigate why and how the citizens implement the SC (Del Cimmuto et al, 2014; Pham Phu et al, 2019), understanding if the population is used to deliver the recyclable waste to the informal collection, which is not still included in the formal MSW management system, as typical in developing countries (Mukherji et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hoi An city, which belongs to Quang Nam province, is a tourist city in the central part of Vietnam with a host of beautiful and unique landscapes and an ancient town designated as a UNESCO World Heritage Site (Pham Phu et al, 2019). The city, with 6,354.9 hectare area, has 13 administrative units, including nine wards (Minh An, Son Phong, Cam Nam, Cam Pho, Thanh Ha, Tan An, Cam Chau, Cam An and Cua Dai), three mainland communes (Cam Ha, Cam Thanh and Cam Kim) and one island commune (Tan Hiep) (Figure 2).…”
Section: Methodsmentioning
confidence: 99%